2007
DOI: 10.1111/j.1748-1090.2007.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐rearing Roe deer Capreolus capreolus: practice and research potential

Abstract: Four ♀ Roe deer Capreolus capreolus were hand‐reared and released into a 10 ha enclosed natural habitat. This paper describes the hand‐rearing procedure, nutrition and development, which we compare with other documented cases. We illustrate the handling techniques that enabled us to maintain a close relationship with the hand‐reared Roe deer in their adulthood and study them under semi‐free‐ranging conditions. The benefits of conducting research with hand‐reared Roe deer are described, together with possible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Only 15/25 neonates, 75% (9/12) of wild boar and 46% (6/13) of roe deer, survived to be released. Hand-rearing a wild ungulate is usually challenging and requires knowledge of the animal's biology, and thus has a very low success rate (36)(37)(38). The handrearing methodology for each species is unique and providing an appropriate milk substitute is one of the most important factors (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 15/25 neonates, 75% (9/12) of wild boar and 46% (6/13) of roe deer, survived to be released. Hand-rearing a wild ungulate is usually challenging and requires knowledge of the animal's biology, and thus has a very low success rate (36)(37)(38). The handrearing methodology for each species is unique and providing an appropriate milk substitute is one of the most important factors (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Roe deer fawns are particularly difficult to hand-rear and the prognosis for fawns brought into captivity is poor (37,38). It has been reported that the success rate of hand-rearing newly born fawns that have not yet consumed milk is close to zero and that of a 1-week old fawn is 50% (37). Moreover, most of the neonates were taken to the VTH several hours or even days after the rescue, when the clinical conditions had become very critical.…”
Section: Discussionmentioning
confidence: 99%
“…The western border of the protected area is delineated by the Sirvan River which is also the Iran-Iraq border. It was designated as a protected area in 1999 to preserve habitat for Eurasian roe deer (Capreolus capreolus) which has been locally extinct in some other countries of the region such as Lebanon, Israel, Syria and Iraq since the beginning of 20 th century, and in Jordan since the beginning of the 19 th century [19]. Forests in the study area are used similarly to forests throughout the Zagros region, primarily for traditional activities such as livestock grazing and browsing, defoliation and disbranching of trees, cutting for fuel and construction, collecting fruits and oak acorns, conversion of forests to dry cultivation land, and utilization of forest products [18].…”
Section: Study Areamentioning
confidence: 99%
“…We have found that local hand-reared female roe deer can maintain a relatively stable body mass throughout the year (Wallach, 2005;Wallach et al, 2007a), and their activity patterns and feeding strategy resemble those of central and northern Europe. They are polyphagic consumers and will switch from browsing to grazing and to fruit/seed consumption, depending on resource availability.…”
Section: Introductionmentioning
confidence: 99%